Learning continuous integration with Jenkins : a beginner's guide to implementing continuous integration and continuous delivery using Jenkins 2 /: a beginner's guide to implementing continuous integration and continuous delivery using Jenkins 2. (2017) - Pathania, Nikhil
No abstract available